Seismic Data Processing and Seismic Inversion in The Ray Parameter Domain: Common Reflection Point (CRP) Stack and Ray Impedance - Wahyu Triyoso; Edycakra Immanuel Sinaga; Madaniya Oktariena (Scientific Contributions Oil and Gas, 2024)
Reservoir characterization can be enhanced by integrating lateral and vertical perspectives from seismic surveys and well logging, respectively. Seismic impedance is a crucial parameter, calculated by multiplying the rock density by the primary (P) wave velocity. While acoustic impedance solely considers these two factors, elastic impedance incorporates additional angular measurements and secondary (S) wave velocity data. Elastic impedance, however, equates the incident angle with the transmission angle in disregard of Snell's law; therefore, it provides a simplified representation of seismic impedance. This study explores an alternative approach to seismic impedance, known as ray impedance. We calculated ray impedance by tracing the impedance variation along the path of a seismic ray, considering its changing velocity and angle as it traveled through different subsurface strata. We transformed the seismic information from the offset space to the ray parameter space, to achieve ray parameter stacking. Unlike the traditional angle domain inversion, which uses near-angle, mid-angle, and far-angle seismic stack data, the ray-impedance inversion utilized segments of ray data: near-ray, mid-ray, and far-ray. We compared the common depth point stack, ray stack, and angle stack methods to infer the acoustic, elastic, and ray impedance characteristics. Challenges with gas cloud interference in seismic data imaging were present. We developed a ray parameter strategy to address these imaging difficulties. The comparison of different stacking techniques indicated that ray stacking could offer an alternative for imaging in the presence of gas cloud effects. Furthermore, impedance cross-plotting demonstrated that ray impedance provided a more discernible separation of low-clay-content zones than elastic impedance did. Overall, data processing in the ray parameter domain yielded positive imaging outcomes in the presence of gas clouds, suggesting that ray impedance is a practical method for lithological differentiation